Systematic Curriculum Management and Teacher Performance Development: A Comparative Case Study in Rural Schools - Sri Retno Kuswahyuni; Ida Tejawiani (Papanda Publisher, 2026)
The implementation of Indonesia's Merdeka Curriculum faces significant challenges in rural schools, particularly regarding teacher performance affected by limited infrastructure and uneven competencies. This study examined how systematic curriculum management through the PDCA (Plan-Do-Check-Act) cycle influences teacher performance development in two rural junior high schools. A qualitative comparative case study was conducted at SMPN 2 Naringgul and SMPN 3 Naringgul, Cianjur Regency, involving 4 school leaders and 28 teachers. Data were collected through observations (84 lessons), in-depth interviews, and document analysis over six months, then analyzed using Miles, Huberman, and Saldaña's interactive model. Both schools successfully implemented varied teaching methods (75% of lessons) and created positive learning environments (89.5%), though digital technology integration remained weak (17.5%). SMPN 2 faced internal-psychological challenges with teacher confidence, while SMPN 3 confronted systemic infrastructure limitations. Academic supervision, formative assessment, and teacher reflection forums functioned effectively, yet documentation practices and systematic follow-up remained inconsistent. Findings demonstrate that PDCA-based curriculum management improves teacher performance when appropriately contextualized, though success depends on addressing both structural constraints and teacher self-efficacy simultaneously. The emergence of organic teacher leadership and adaptive management strategies proved crucial for implementation success. Results underscore the necessity of differentiated support approaches, job-embedded professional development, and sustained multi-year commitments to technology integration in resource-constrained rural contexts.